The Relative Abundance of Benthic Bacterial Phyla Along a Water-Depth Gradient in a Plateau Lake: Physical, Chemical, and Biotic Drivers - Wu, Kaiyuan; Zhao, Wenqian; Wang, Qian; Yang, Xiangdong; Zhu, Lifeng; Shen, Ji; Cheng, Xiaoying; Wang, Jianjun (Frontiers in Microbiology, 2019)
Water-depth biodiversity gradient, one of the typical biogeographical patterns on Earth, is understudied for bacteria in freshwater ecosystems, and thus left the underlying mechanisms understood especially for benthic bacteria. Here, we investigated the water-depth distribution of surface sediment bacteria phyla and their driving factors in Lake Lugu, a plateau lake in southwest China. Our results revealed that the relative abundance of 11 dominant bacterial phyla showed various water-depth patterns, such as increasing, decreasing, hump-shaped and U-shaped patterns. These patterns across phyla were consistent with their different niche positions of water depth, while the occupancy-abundance relationships were not dependent on phylum attributes. Consistently, phylum abundance was best explained by water depth, other physical and chemical factors, such as metal ion concentrations, SiO2 and pH, can also explain the variations in some bacterial phyla. Chemical variables were the main drivers of the dominant bacterial phyla. However, biotic variables also showed substantial importance for some phyla, such as Planctomycetes, Actinobacteria and WS3. This work could provide new insights into the general water-depth patterns and underlying mechanisms of the relative abundance of bacterial phyla in freshwater ecosystems.